Food defense management practices in private country clubs - Olds, David A. (Kansas State University, 2010)
The purpose of this study was to survey country club professionals’ importance perceptions of food defense and the frequency with which preventive practices were implemented in their clubs to prevent bioterrorism. Gaps between importance perceptions and practice frequency were compared with concern of food terrorism and practice frequency implementation. Perceived self-efficacy measures and perceived barriers were compared with motivations to develop a food defense management plan and practice frequency implementation. Importance perceptions and practice frequencies were studied to ascertain if there were differences among operational factors. Club professionals with smaller gaps implemented preventive practices more frequently. Club professionals with higher self-efficacy levels were more motivated to develop food defense management plans and implemented preventive practices more frequently. Club professionals with higher barriers were less motivated to develop food defense management plans and implemented preventive practices less frequently. The field study component investigated food security practices in private country clubs. Club manager interviews and observations of operational practices were conducted. Most club managers stated that they did not think their clubs were at risk of a bioterrorist attack. Cost and lack of need were identified as barriers towards implementing a food defense management plan. Club employees were perceived to be more likely to initiate a bioterrorism attack than non-employees. Background checks and good employment practices were perceived as effective in increasing food security in clubs. Most clubs did not monitor arrivals and over half did not secure their chemicals. Based on the results of the field study, the researcher recommended several actions that could improve food security in country clubs including installing video surveillance and developing disaster management plans that include food defense. Recommendations for future research included continued examination of club managers’ self-efficacy perceptions towards biosecurity and identifying barriers to food defense implementation in other retail foodservice segments.
Keywords: Bioterrorism; Food; Defense; Country; Club; Managers; Operations Research (0796)